"Difference which makes a difference" (Bateson, 1972): how the neurodiversity paradigm and systemic approaches can support individuals and organisations to facilitate more helpful conversations about autism. Issue 1 (2nd January 2023) - Long, Éilis
ABSTRACT: This article explores the possibilities for systemic approaches in supporting a neurodiversity perspective, and how these lenses may improve social workers' abilities to support autistic people. These ideas are rooted in an Action Research project I undertook, as an autistic practitioner-researcher, in a statutory children's services department of a UK Local Authority. Social workers are very likely to encounter autism in their work. Autism is widely misunderstood, often misrepresented, and carries a persisting social stigma, but neurodiversity offers a new paradigm for appreciating and understanding autism as part of a person's diversity, bringing strengths and challenges (Haney, pp. 63–64). Social workers are mandated to advocate for the rights of oppressed groups and promote diversity in all its forms. Therefore, reflecting on presumed knowledge and challenging deficit-driven dominant discourses about autism that currently govern practice should be part of all good social work practice. The findings of my project, and subsequent reflections call for UK social workers, local authorities and social work education programmes to embrace neurodiversity, which can be aided by systemic approaches and techniques.